Mobile application system for cardiovascular disease patient / Nurul Azwa Atikah Ahmad Tarmizy and Abdul Hapes Mohammed - Ahmad Tarmizy, Nurul Azwa Atikah; Mohammed, Abdul Hapes (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Cardiovascular failure is a complex and potentially fatal chronic condition that requires medical and lifestyle therapy. Unfortunately, there are not many mobile fitness application systems for cardiovascular disease (CVD) patients. Therefore, the purpose of this study is to develop a mobile application system to guide cardiovascular disease (CVD) patients about exercise that is suitable for them. The mobile health application system can be used by heart patients to find out the most accurate and safe exercise methods. In this mobile application, patients can exercise using a stopwatch to record the time they exercise, such as walking, running, cycling, and climbing stairs. Then, patients can know their BMI according to their height and weight. In addition, patients can also find out information about heart disease in this mobile application. The scope focuses on all patients with cardiovascular disease, no matter if they are children, teenagers, adults, or the elderly, who can use this mobile application system to exercise. In addition, this mobile application uses the DSRM method, which is the Design Science Research Methodology, for development. After that, the results and findings for this mobile application are derived from evaluation results from expert reviews and in-depth interviews with patients and regular users. The test results revealed that this mobile application is usable but needs to be refined and improved. As a result, CPFitness has achieved its objective and goal of developing a mobile fitness application system for patients with cardiovascular disease (CDV).